2015
DOI: 10.1093/neuonc/nov310
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein signaling promotes tumorigenesis in a murine model of high-grade glioma

Abstract: BMP inhibition may represent a viable therapeutic approach in adult HGG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Steinert et al 33 found through in vitro experiments that: in breast cancer cells with normal nutrition, BMP2 can promote the occurrence of apoptosis by transcription of apoptosis-related genes (such as PKR, EIF2α); in breast cancer cells with malnutrition, BMP2 can generate ID-1 through the MAPK signal transduction pathway and inhibit the activation of Caspase-3 to enhance the viability of breast cancer cells. This phenomenon suggests that there should be some type of cell homeostasis mechanism in the process of tumor morphogenesis to regulate the induction or inhibition mediated by BMP 11 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Steinert et al 33 found through in vitro experiments that: in breast cancer cells with normal nutrition, BMP2 can promote the occurrence of apoptosis by transcription of apoptosis-related genes (such as PKR, EIF2α); in breast cancer cells with malnutrition, BMP2 can generate ID-1 through the MAPK signal transduction pathway and inhibit the activation of Caspase-3 to enhance the viability of breast cancer cells. This phenomenon suggests that there should be some type of cell homeostasis mechanism in the process of tumor morphogenesis to regulate the induction or inhibition mediated by BMP 11 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that BMP signalling is active in the majority of high-grade glioma (HGG) cells obtained from adult patients [55]. Moreover, consistent with a role of BMP signalling in human HGG, deletion of BMPR1A (ALK3) in oncogenic mouse astrocytes resulted in decreased proliferation, invasion and migration.…”
Section: Role Of Bmp Signalling In Cancer Pathogenesismentioning
confidence: 76%
“…Smad4 is also an indispensable element of the bone morphogenetic protein (BMP)-signaling pathway. The BMP signaling pathway has been shown to promote tumorigenesis in a murine model of high-grade glioma (35). In addition, Smad4 protein is highly expressed in glioma; therefore, Smad4 is a crucial target gene in the treatment of glioma.…”
Section: Discussionmentioning
confidence: 99%